2013
DOI: 10.1186/2052-336x-11-36
|View full text |Cite
|
Sign up to set email alerts
|

Two stage treatment of dairy effluent using immobilized Chlorella pyrenoidosa

Abstract: BackgroundDairy effluents contains high organic load and unscrupulous discharge of these effluents into aquatic bodies is a matter of serious concern besides deteriorating their water quality. Whilst physico-chemical treatment is the common mode of treatment, immobilized microalgae can be potentially employed to treat high organic content which offer numerous benefits along with waste water treatment.MethodsA novel low cost two stage treatment was employed for the complete treatment of dairy effluent. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Microalgae and culture medium C. pyrenoidosa was collected from Department of Biotechnology, IIT Roorkee and grown in BG11 culture medium (without adding carbon source) (Park et al 2011;Yadavalli and Heggers 2013).The composition of BG11 media are given in Tables 1 and 2 as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Microalgae and culture medium C. pyrenoidosa was collected from Department of Biotechnology, IIT Roorkee and grown in BG11 culture medium (without adding carbon source) (Park et al 2011;Yadavalli and Heggers 2013).The composition of BG11 media are given in Tables 1 and 2 as follows:…”
Section: Methodsmentioning
confidence: 99%
“…According to the study on N 15 -labeled fertilizer, cyanobacteria assimilate more nitrogen than chemical fertilizer and are more reliable for rice plant cultivation (Fernández Valiente et al, 2000). Another exciting research on immobilized Chlorella pyrenoidosa on dairy waste effluent as a biofertilizer gives a 30% surge in paddy root and shoots length (Yadavalli and Heggers, 2013). A study also found a yield of 650 mg L −1 of Chlorella sp.…”
Section: Biofertilizermentioning
confidence: 99%
“…The beads settle rapidly or can be separated from wastewater by sieving, simplifying harvesting of the algae . The beads can then be used directly as fertilizer or digested for biomethane production . Furthermore, cultivation in beads protects the culture from harmful contaminants in the wastewater and enables selection of an algal species which has favourable nutrient removal traits or high value for product recovery without risk of the species becoming contaminated over time .…”
Section: Introductionmentioning
confidence: 99%